Outcomes of the Keystone Island Perforator Flap: A Systematic Review - Weinberg, Maxene; Heiman, Adee J.; DeSanti, Rebecca; Lanni, Michael A.; Kouwenberg, Emily Van; Patel, Ashit (Journal of Reconstructive Microsurgery, 2022)
Background The Keystone Design Perforator Island Flap (KDPIF), first described by Behan in 2003, has been demonstrated as a versatile, safe, and straightforward reconstructive option for various soft tissue defects. The purpose of this systematic review is to evaluate the indications, variations, and overall complication profile of the keystone flap in reconstructive surgery.Methods A literature review was conducted in accordance with PRISMA guidelines using MeSH term “surgical flaps” with the keyword “keystone flap.” Empirical studies with at least 15 patients who underwent keystone flap reconstruction were assessed for quantitative analysis. Outcomes of interest included patient demographics, indications, anatomic location, flap design, and complications.Results Database search produced 135 articles, of which 25 were selected for full-text review. Out of 23 studies selected qualitative analysis and 22 met criteria for quantitative analysis. Overall success rate of this flap was 98%. Wound complications were highest in extremity flaps. Several modifications of this flap were described.Conclusion Keystone reconstruction demonstrates excellent success rates and versatility. However, further studies with more standard reporting are needed to determine guidelines for patient specific surgical planning.
Keywords: keystone flap; perforator flap; reconstructive surgery